Phthalide metabolites produced by mangrove endophytic fungus Pestalotiopsis sp. SAS4 - Peng, J.; Chen, P.; Li, C.; Liu, J.; Sun, Y.; Yang, M.; Tao, Y.
Two new phthalide derivatives (1-2)and four known phthalide compounds (3-6)were purified from the culture of a mangrove endophytic fungus Pestalotiopsis sp. SAS4. Their chemical structures were established by analyses of 1D and 2D nuclear magnetic resonance (NMR)and high resolution mass spectrometry (HR-MS)spectroscopic data. All of these compounds were evaluated in vitro for antibacterial, cytotoxicity, and resistance to hypoxic-ischemic injury activities.